2018
DOI: 10.1038/s12276-018-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib resistance in hepatocarcinoma: role of hypoxia-inducible factors

Abstract: Sorafenib, a multikinase inhibitor with antiproliferative, antiangiogenic, and proapoptotic properties, constitutes the only effective first-line drug approved for the treatment of advanced hepatocellular carcinoma (HCC). Despite its capacity to increase survival in HCC patients, its success is quite low in the long term owing to the development of resistant cells through several mechanisms. Among these mechanisms, the antiangiogenic effects of sustained sorafenib treatment induce a reduction of microvessel de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
232
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 261 publications
(233 citation statements)
references
References 58 publications
1
232
0
Order By: Relevance
“…Despite its efficacy, resistance emerges soon after initial treatment, but the mechanism is still unclear. Studies had focus on PI3K/AKT 5 , JAK/STAT pathways, hypoxia-inducible pathways 6 , and epithelial-mesenchymal transition 7 . Studies revealed that microRNAs (miRNAs) may have an important role in this resistance 8 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its efficacy, resistance emerges soon after initial treatment, but the mechanism is still unclear. Studies had focus on PI3K/AKT 5 , JAK/STAT pathways, hypoxia-inducible pathways 6 , and epithelial-mesenchymal transition 7 . Studies revealed that microRNAs (miRNAs) may have an important role in this resistance 8 as well.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, systemic therapy is used, utilizing two available tyrosine kinase inhibitors (TKIs), sorafenib and lenvatinib, in the first-line setting for advanced HCC [16]. Regardless of its effectiveness, liver cancer cells are able to develop sorafenib resistance after sustained administration [17], where several TKIs (regorafenib and cabozantinib) and monoclonal antibodies (nivolumab, pembrolizumab and ramucirumab) have been recently approved [16]. Considering toxicity and adverse reactions caused by these chemotherapeutic agents, some investigations have focused on the study of antitumor effects of natural compounds against HCC, such as resveratrol, curcumin and melatonin [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it reduces the proliferation and migration of tumor cells; thus, it prolongs HCC patients' survival [11,37]. Despite the progress achieved, the observed survival was found to be dependent on the patients' individual sensitivity, and it lasts for one year at most [38,39]. In 2017, regorafenib (II) was approved by the FDA for the treatment of HCC patients whose therapy was not successful with sorafenib (I) [40,41].…”
mentioning
confidence: 99%